Anti‐Cancerous Brucine and Colchicine: Experimental and Theoretical Characterization. Issue 39 (21st October 2019) - Afzal, Aboothahir; Thayyil, Mohamed Shahin; Shariq, Mohammad; Mary, Yohannan Sheena; Resmi, Kaippallil Sundaresan; Thomas, Renjith; Islam, Nasarul; Abinu, Ajithan Jyothi
Abstract: Brucine and colchicine are alkaloids, which are found abundantly in Asian Countries, having medicinal values in Ayurveda and is used widely in China. But surprisingly, it is reported recently in the literature that both brucine and colchicine possess anti‐cancerous effects. A comprehensive quantum computational study of brucine and colchicine to determine its structural and electronic properties is lacking in the literature. The optimized molecular geometries, electronic and vibrational spectral analysis, Frontier Molecular orbital analysis, natural bonding orbitals (NBO), non linear optical properties (NLO), Vibrational circular dichroism (VCD) spectra were studied by Density Functional Theory (DFT) method by Computational Chemistry tool Gaussian‐09 with B3LYP/6‐311++G(d, p) basis set. Relaxed energy scans on dihedral angles in brucine and colchicine were performed to generate potential energy surfaces (PES) corresponding to rotational motions for conformational analysis. Theoretical Light Harvesting Efficiency (LHE) parameter for different halogen substitutions for brucine and colchicine were determined by TD‐DFT method. Molecular electrostatic potential surfaces (MEP) of the title compounds were generated to find the reactive molecular sites. Nonlinear optical properties (NLO) analysis showed that the first hyper polarizability values of brucine and colchicine are 25.56 and 22.15 times than that of urea. The in‐silica molecular docking analysis of brucine and colchicine were done using the Maestro ‐ Schrodinger suite 8.0 with cancer target proteins. Abstract : Brucine and colchicine are anti‐cancerous alkaloids. Molecular docking proved that brucine showed a lowest binding affinity of −8.218 kcal/mol with cancer protein with PDBID 5JMJ, while colchicine showed a lowest binding affinity of −5.298 kcal/mol with cancer protein with PDBID 3 S7 S and also showed a binding affinity of −4.68 kcal/mol with cardiovascular protein 5G3 N. Thus the molecular docking results point out that the reported facts that brucine and colchicine have anti‐cancer effects. The frontier molecular orbitals HOMO‐LUMO energy gap for colchicine is calculated as 3.649 eV and 4.831 eV for brucine.